STRATEGI PEMBERANTASAN BUTA HURUF MELALUI SPAS PADA MASYARAKAT TOMBOLO KABUPATEN GOWA - Arfenti Amir; Akhiruddin Akhiruddin; Eka Fitriana (JPM PAMBUDI, 2019)
The aim of this community services was conducted to sharpen of respondents’ sensitivity and the ability to identify, understand, interpreter, make, communicate, and count. In the end of this program, to involve the learning continuously in which individuals probably got their goals, to develop their knowledge and capacity, and full participation of their community and in whole community. Method was applied in this program namely method that emphasized the respondents’ participation. There were three steps in implementing the programs namely: (1) planning, (2) action, (3) evaluation stages. There were 40 respondents from their ages beginning from 12 to 55 years old and they had productive age. The results of this community services, there were increasing respondents’ literacy each kinds of community services more than 70%. Based on post test results showed that there were 90% (36 respondents) had to be able to read, 92% (37 respondents) had to be able to write, and 85% (34 respondents) had to be able to count. 87.5% (35 respondents) had to be able to read Al-Quran. Based on the results obtained from this community service program, so it was stated success to motivate community got out from illiterate.